The Influence of Work Discipline and Motivation on Teacher Performance with Work Spirit as an Intervening Variable in Teluk Mengkudu District - Syafril Gunawan; Kiki Farida Ferine (Lafadz Jaya Publisher, 2025)
In education, teacher performance is a key factor in determining the success of the learning process in schools. High-performing teachers are not only able to create a conducive learning environment but also design innovative learning strategies, adapt teaching methods to student needs, and utilize technology in the learning process. The results of this study are as follows: Work discipline has a positive and significant effect on teacher performance with an original sample value of 0.232 and p values of 0.013. Work discipline has a positive and significant effect on work enthusiasm with an original sample value of 0.234 and p values of 0.029. Motivation has a positive and insignificant effect on teacher performance with an original sample value of 0.140 and p values of 0.093. Motivation has a positive and significant effect on work enthusiasm with an original sample value of 0.698 and p values of 0.000. Work enthusiasm has a positive and significant effect on teacher performance with an original sample value of 0.620 and p values of 0.000. Work discipline has a positive and significant effect on teacher performance through work enthusiasm with an original sample value of 0.145 and p values of 0.029. Motivation has a positive and significant effect on teacher performance through work enthusiasm with an original sample value of 0.433 and p values of 0.000.